Valoración del riesgo de deforestación fututa en Costa Rica. - Chaves Esquivel, Edwin (2001)
The article presents a procedure to estimate the future risk of deforestation in Costa Rica. It uses a geographic information system with data layers in “raster” format with cells of 750 m side. The Costa Rican territory comprises about 100,000 cells, including 34,000 in forests in the early 1980s. An explanatory model of the probability of deforestation in 1984-1996 is identified using logistic regression. This model is then applied to demographic data updated to 1996 to estimate the expected probabilities of deforestation of those cells forest-covered in 1996. About 4,000 km2 of 1996 forests are in risk of deforestation in the following 15 years. Of the remaining 15,000 km2 of forests, 73% are in protected areas. Most forests outside protected areas are at high risk of clearing in the coming 15 years. These high-risk forest lands are located mostly in the northern Pacific region, the Caribbean coast and the northern plains. According to the model, the cells at risk of deforestation have 44% likelihood of being, in fact, cleared (if certain past conditions remain constant). These results are a call upon what could happen due to the increased demographic pressure in Costa Rica, if such pressure is not neutralized with appropriate policies.